Studi Eksperimental Twin Waterjet Thruster Menggunakan Thermoplastic Polyurethane (TPU) yang Diproduksi dengan 3D Printing - Muhamad Aris; Pristiansyah; Ramli; Sugianto; Ferzy Ersandy; Achmad Rusdy; Hafiz Fadhil; Muhammad Subhan; Hasdiansah Hasdiansah (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2026)
Indonesia, as the world’s largest archipelagic nation, requires efficient and reliable marine propulsion systems to support sustainable transportation. The waterjet thruster has emerged as an alternative to conventional propellers due to its advantages in maneuverability, cavitation resistance, and operational efficiency. With the advancement of additive manufacturing, particularly 3D printing, opportunities have arisen to fabricate propulsion components using innovative materials such as Thermoplastic Polyurethane (TPU), which combines flexibility and durability.This study presents the design, fabrication, and experimental testing of a twin waterjet thruster produced with TPU material through the Fused Deposition Modeling (FDM) method. Performance tests were conducted using a 22 HP combustion engine at 4,100 rpm. The experimental results indicate that the thrust generated ranged between 10.8–12 kg (equivalent to 105.94–117.72 N) with an average thrust of 11.36 kg (111.24 N). These outcomes demonstrate that the system delivers consistent performance with minimal variation between trials. The findings confirm the feasibility of TPU-based twin waterjet thrusters for small to medium-scale marine applications and provide a basis for further development toward environmentally friendly propulsion systems through design optimization and the integration of electric motors.